Expansion of the mutation spectrum and phenotype of USP7-related neurodevelopmental disorder - Zheng, Hong; Mei, Shiyue; Li, Fuwei; Wei, Liwan; Wang, Yanchu; Huang, Jinrong; Zhang, Feng; Huang, Jia; Liu, Yanping; Gu, Weiyue; Liu, Hongyan (Frontiers in Molecular Neuroscience, 2022)
Background Hao-fountain syndrome (HAFOUS) is a neurodevelopmental syndrome characterized by global developmental and severe language delays, behavioral abnormalities (including autism), and mild dysmorphic impairment of intellectual development. It is a dominant genetic disease caused by USP7 gene (*602519) mutations on chromosome 16p13.2. So far, only 15 cases with 14 deleterious variants in the USP7 gene have been reported. Materials and methods This study describes three unrelated patients with USP7 variants. Besides, we identified novel de novo heterozygous USP7 variants using trio-whole exome sequencing and verified by Sanger sequencing. Furthermore, clinical characteristics were evaluated by reviewing the medical records. Results The three identified variants, i.e., one frameshift variant (c.247_250del, p.Glu83Argfs × 18) and two missense variants (c.992A > G, p.Tyr331Cys; c.835T > G, p.Leu279Val) are unreported. The predominant clinical manifestations of the three patients included: DD/ID; language impairment; abnormal behavior; abnormal brain magnetic resonance (dilation of lateral ventricles, dilation of Virchow-Robin spaces, dilated the third ventricle, abnormal cerebral white matter morphology in bilateral occipital lobes, hypodysplasia of the corpus callosum, arachnoid cyst, delayed myelination, and widened subarachnoid space); some also had facial abnormalities. Conclusion In summary, DD/ID is the most prevalent clinical phenotype of HAFOUS, although some patients also exhibit language and behavioral abnormalities. For the first time in China, we identified three variants of the USP7 gene using whole-genome sequence data. This work expands the USP7 gene mutation spectrum and provides additional clinical data on the clinical phenotype of HAFOUS.